Kajian Pengaruh Total Resistance Terhadap Produktivitas Pengangkutan Batu Kapur Di Front C PT. Semen Padang, Kecamatan Lubuk Kilangan, Kota Padang, Sumatera Barat - Syarifa Amalia; Dedi Yulhendra (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. PT. Semen Padang is a limestone mining company located in Bukit Karang Putih, Indarung, Padang City, West Sumatera using the quarry mining method. Production in October 2019 on Front C was 139.590 tons while the production target was 307.440 tons. One of the factors that influence the productivity of the conveyance is the total resistance, namely rolling resistance and grade resistance. The lowest total resistance value when loaded is in the M-20-21 segment at -2,8% while the largest in the M-5-6 segment is -14,1%. The smallest total resistance value when empty is in the M 3-2 segment by 0,47515% while the largest in the M 2-1 segment is 21,5717%. After simulating the total resistance value, the total resistance value obtained when the smallest load is in the M 8-9 segment is -2% while the largest in the 3-4 M segment is 9,3%. The smallest total resistance value when empty is in segments M 20-19 is 15,77%. With the increased productivity of the conveyance from 375.300 tons/hour/ unit with a cycle time of 25,53 minutes to 437.880 tons/ hour/unit with a cycle time of 21,88 minutes.Keywords: Production, Productivity, Total resistance, Rolling Resistance, Grade Resistance, and Cycle Time